Persistence patterns among secondary STEM teachers: a comparative study of Noyce scholar cohorts in face-to-face and blended learning environments amid the pandemic - Kurz, Terri L.; Ganesh, Tirupalavanam; Covert, Jason; Nation, Marcia L. (Frontiers in Education, 2025)
Noyce scholars were provided funding to compete teaching certification in STEM and earn a master’s degree. Then, they were required to teach for 2 years in a Title I school setting. All cohorts were impacted by the pandemic (e.g., university coursework, student teaching and/or teaching was converted to blended learning). This study highlights the differences in teaching persistence across the three cohorts of scholars (n = 24) regarding continuance in earning their degrees and completing their two-year teaching obligation. Descriptive case study methodology was used in this comparative study across three cohorts. The primary research question explored how different modalities of initial teaching experiences impact early persistence among secondary STEM teachers. The supplemental research question explored scholars’ intention to remain in the teaching profession. Results indicated that the cohort with blended first year teaching experiences had the lowest persistence rate. Generally, scholars intend on persisting in the profession for 6 years or more. Recommendations for practice include the need for more traditional, face-to-face initial teaching experiences and a cohort model for new teachers. Recommendations for research include continued evaluation of Noyce projects, longitudinal studies to track STEM teachers’ persistence, and a comprehensive analysis of teacher preparation programs’ effectiveness in promoting teacher retention.